SITUATION OF UNCERTAINTY: PRAGMATIC, SEMANTIC, AND SYNTACTIC ASPECTS OF INVESTIGATION - Topka, Larisa V. (European Scientific Journal, ESJ, 2013)
The paper focuses on uncertainty as a complex and multifaceted phenomenon which is analyzed from the pragmatic, semantic, and syntactic points of view, therefore in the semiotic domain of language. Pragmatic aspect of the investigation of uncertainty phenomenon displays the regulation of speech behaviour with the help of a tactics-situational approach to describing the communicative interactions. Semantic aspect of the research indicates uncertainty as an abstract semantic formation (conceptual structure) or, in terms of cognitive linguistics, a prototypical situation made by a definite number of semantic segments as its components. Syntactic aspect of the investigation presents means of its (uncertainty) linguistic representation – an uncertain statement which rests on a particular bulk of lingual means of expression that are perfectly adapted to its realization and affects the addressee’s behaviour with the help of hesitancy, courtesy, understatement, and unpredictability.